Determinação multielementar em amostras de água da bacia do Rio Doce após o acidente da barragem de fundão - Caroline Ferreira Saldanha (2018)
Preliminary analyzes of water samples soon after the dam broke revealed the presence of metals at high concentrations in the river at various points and it is known that prolonged exposure to metals such as lead, iron, nickel, manganese, mercury, copper , selenium, zincand the metalloid arsenic can cause various damage to human health. This work has as main objective to evaluate if the water of consumption of cities supplied with waters impacted by the residue from the rupture of the dam of Fundão is within the established standards for metals and metalloids and to seek correlations between the measured parameters. The concentrations of the total metals Ag, Al, Ba, Be, Cd, Co, Cr, Cu, Fe, Hg, Li, Mn, Ni, Pb, Se, Tl, V and total metalloids Sb and As in samples of water used for consumption and Al, Fe and Cu dissolved in samples of river waters and lagoons. A total of 70 samples were collected in four cities affected by the dam rupture mud: Barra Longa (MG), GovernadorValadares (MG), Colatina (ES) and Linhares (ES), at different times during the years 2016 and 2017 The samples were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). After the optimization of the equipment and the validation of the analyticalprocedure, the results obtained were compared to the limits established for drinking and gross water according to the current legislation. Multivariate statistical analysis tools (PCA and HCA) were used in order to verify the similarity of the collected samples, increasing theunderstanding of the behavior of the data set. From the well samples studied, 46.2% presented some type of violation of the maximum values allowed by Ministry of Health Ordinance No. 2914 for Al, Fe, Ni, Mn and Pb. Treated water samples presented 18.4% of violations of values In the case of raw water samples from the river, 36.4% showed aviolation of the maximum permitted values for Al and Fe dissolved and those from lakes / springs, 66,6% presented a violation to Ferro dissolved under Resolution No. 357 of CONAMA for class 2 waters.